Effects of hormonal contraceptives on lipid profile among women attending family planning unit in Goba Town Public Health Facilities, Bale, Southeast Ethiopia: a comparative cross-sectional study - Awel Turki; Almaz Ayalew; Andualem Mossie; Shimelis Mitiku (BMC, 2023)
Abstract Background Hormonal contraceptives are a widely used contraceptive method for the prevention of pregnancy in women. It is associated with change in lipid profile which results in congestive heart failure, coronary heart disease, angina, deep vein thrombosis and stroke which are the major cause of premature death. We aim to investigate the effects of hormonal contraceptive use on lipid profile among women attending family planning unit in Goba Town Public Health Facilities. Methods A comparative cross-sectional study design was conducted on 93 hormonal contraceptive users and 93 non-users' women in Goba Town Public Health Facilities from September to November, 2022. Blood samples for the estimation of TC, TG, HDL-c and LDL-c levels were collected. Student's independent t-test was used to compare the results of lipid profiles. One-way ANOVA was used to identify the variation of lipid profile between progestin only pills, DMPA and implant users. Simple linear regression was used to determine the change in lipid profiles in relation to the duration of hormonal contraceptive use. P-value less than 0.05 was considered as statistically significant. Result The mean serum level of TC, TG and LDL-c was significantly increases in hormonal contraceptive users in comparison with non-users. The mean serum level TC, TG, LDL-c and HDL-c was significantly different between DMPA, implanon and POP users. The mean serum level of TC, TG and LDL-c in implanon users was lower than DMPA and POP users. As the duration of DMPA and POP use increases, the serum level of TC, TG and LDL-c were significantly increased. But, the serum level of HDL-c was significantly decreased. LDL-c was significantly increased with the duration of implanon use. Conclusion The mean serum level of TC, TG and LDL-c were significantly increased among hormonal contraceptive users. The mean serum level of lipid profile was significantly different between DMPA, implanon and POP users. The serum level of TC, TG, LDL-c were directly proportional to the duration of DMPA and POP use. Routine evaluation of lipid profiles is advisable before and after initiation of hormonal contraceptives.